Особенности ремоделирования сердца у больных с разными клиническими формами неклапанной фибрилляции предсердий - Сыволап, В. Д.; Лашкул, Д. А.; Марченко, В. В.; Сиволап, Віктор Денисович; Лашкул, Дмитро Андрійович; Марченко, Валерія Василіївна (My University, 2015)
Изучены структурно-функциональные особенности сердца у 80 пациентов с разными клиническими фор- мами неклапанной фибрилляции предсердий. Прогрессирующее течение от пароксизмальной к постоян- ной форме фибрилляции предсердий характеризуется снижением толерантности к физической нагрузке, увеличением индекса массы тела, диаметра левого и правого предсердий, преобладанием прогностически неблагоприятных типов ремоделирования, снижением сократительной способности левого желудочка. According to the population studies the prevalence of atrial fibrillation (AF) is near 2 %, increases to the 9 % in persons older than 80 years. The character of structural-functional cardiac remodeling in patients with the different forms of AF is insufficiently studied for today. Aim of research. To study the special features of the structural-functional cardiac remodeling in patients with the different forms of the non-valvular arterial fibrillation. Materials and methods. There were examined 80 patients with AF (46 men and 34 women) 36–85 years old (the mean age 63,36±1,1 years). According to the aim of research all patients were divided into three groups depending on the clinical form of AF (paroxysmal, persistent and permanent). All patients underwent the standard general clinic examination, electrocardiography, echocardiography. Results. In patients with paroxysmal form of AF took place the clinically less apparent heart failure comparing with persistent and permanent ones. Structural-functional state of myocardium at the permanent form of AF was characterized with the increase of left and right atrium diameter, left atrium volume index, left ventricle final-diastolic volume, systolic pressure in the pulmonary artery comparing with the paroxysmal and persistent ones. In the group with permanent form of AF in 71,43 % was detected the eccentric hypertrophy of the left ventricle. Conclusion. Progressing clinical course from the paroxysmal to the permanent atrial fibrillation is characterized with the decrease of tolerance to the physical load, increase of the body mass index, left and right atrium diameter, predominance of prognostically unfavorable types of remodeling.
Keywords: фибрилляция предсердий; прогрессирование заболевания; факторы риска; ремоделирование сердца; диастолическая функция; внутрішня медицина; arterial fibrillation; progressing of disease; risk factors; cardiac remodeling; diastolic function